1985
DOI: 10.1111/j.1469-8986.1985.tb01632.x
|View full text |Cite
|
Sign up to set email alerts
|

The Standardized Mental Stress Test Protocol: Test‐Retest Reliability and Comparison with Ambulatory Blood Pressure Monitoring

Abstract: The mental stress test protocol is used extensively in research, but different laboratories often employ different stress tasks, utilize different dependent variables to index the stress response, and perform different transformations on the gathered data. The present study determined the test‐retest reliability of 11 cardiovascular dependent variables during a resting baseline and three common stress tasks: playing a video game, performing a choice reaction‐time test, and performing a cold‐pressor test. Sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(39 citation statements)
references
References 25 publications
5
33
0
1
Order By: Relevance
“…Research evaluating the association between high cardiovascular reactivity to laboratory psychological stressors and real-life events using ambulatory monitoring has begun, and this line of evidence will also help clarify this issue. 37 ' 38 However, additional longitudinal studies on the long-term significance of high reactivity to psychological stress in blacks and whites are still needed and appear well warranted. These investigations may be more productive if the cardiovascular reactivity factor is evaluated in interaction with indices of stressful life demands, such as occupation, socioeconomic status, and family situation.…”
Section: Discussionmentioning
confidence: 99%
“…Research evaluating the association between high cardiovascular reactivity to laboratory psychological stressors and real-life events using ambulatory monitoring has begun, and this line of evidence will also help clarify this issue. 37 ' 38 However, additional longitudinal studies on the long-term significance of high reactivity to psychological stress in blacks and whites are still needed and appear well warranted. These investigations may be more productive if the cardiovascular reactivity factor is evaluated in interaction with indices of stressful life demands, such as occupation, socioeconomic status, and family situation.…”
Section: Discussionmentioning
confidence: 99%
“…Although van Doornen (1986) examined students' HRR to an examination, and Matthews et al (1986a) measured adolescents' HRR to giving a speech, neither of those studies collected data on the frequency of HRR during typical daily events. Thus, although there are several studies of the generalizability of laboratory based blood pressure reactivity to ambulatory blood pressure taken over several hours (e.g., Harshfield et al, 1988;McKinney et al, 1985;Watson et aL, 1980), the issue of the generalizability of laboratory-based HRR to everyday life events in terms of frequency of occurrence has received little attention.…”
Section: Introductionmentioning
confidence: 98%
“…First, we did not randomize the order of psychophysiological tasks. However, previous research suggested that the reliability of psychophysiological tests in nonrandomized protocols is satisfactory [McKinney et al, 1985]. Second, imagery exposure may not be strong enough to evoke anxiety about specific situations.…”
Section: Discussionmentioning
confidence: 97%